Sexual Object or Sexual Subject? Media Use, Self-Sexualization, and Sexual Agency Among Undergraduate Women. (March 2018) - Ward, L. Monique; Seabrook, Rita C.; Grower, Petal; Giaccardi, Soraya; Lippman, Julia R.
Objectification theorists argue that repeated exposure to sexually objectifying media content leads to higher levels of self-objectification. Although consequences of self-objectification for women's sexual health and sexual agency have been proposed, efforts to test these connections have been infrequent and have yielded inconsistent results. We used structural equation modeling to test connections between exposure to three media genres (women's magazines, lifestyle reality TV, and situation comedies), self-sexualization, and four dimensions of sexual agency among 754 heterosexual and bisexual undergraduate women aged 16–23 ( M = 18.5). Our assessments of sexual agency focused on sexual assertiveness, condom use self-efficacy, sexual affect, and alcohol use to feel sexual. Findings confirmed our expectations. More frequent consumption of women's magazines, lifestyle reality TV programs, and situation comedies each predicted greater self-sexualization, which in turn predicted greater use of alcohol to feel sexual, less condom use self-efficacy, and more negative sexual affect. We discuss implications for women's sexual well-being and for research on media sexualization. We also offer suggestions for practitioners, parents, and educators to disrupt the associations among media use, self-sexualization, and diminished sexual agency. Online slides for instructors who want to use this article for teaching are available on PWQ's website at http://journals.sagepub.com/page/pwq/suppl/index